A comprehensive meta-analysis on Problematic Facebook Use. (June 2018) - Marino, Claudia; Gini, Gianluca; Vieno, Alessio; Spada, Marcantonio M.
Abstract: In recent years, researchers have been showing an increasing interest in the conceptualization of problematic Facebook use, and its associations with individual characteristics. The present meta-analysis aimed to summarize the findings of the recent literature on this topic with the aim of understanding the specific features of this phenomenon (that is, its associations with the time spent online and the broader concept of Internet addiction), and the individual characteristics of Facebook users (including gender differences, personality traits, self-esteem levels, and motivations for using Facebook). The sample included 56 independent samples with a total of 27, 867 participants (59.22% females; mean age = 23.94 years ( SD = 4.75). Briefly, results showed a small gender effect favoring females and a positive association between problematic Facebook use, time spent online and Internet addiction, whereas a negative association was found with self-esteem. Neuroticism and conscientiousness were the most clearly personality traits associated with problematic Facebook use, and the strongest associations observed between problematic Facebook use and motives with internal source and motives with negative valence. This comprehensive meta-analysis makes contributions to understanding the phenomenon of problematic Facebook use and its relation with individual characteristics. Highlights: PFU is positively linked to Internet addiction and time spent online. PFU is negatively associated with self-esteem. PFU is clearly positively associated with neuroticism and conscientiousness. PFU is positively associated with motive for using Facebook.